134k views
5 votes
What is the solution to the equation 4x + 2(x – 3) = 3x + x – 12? (1 point)

–3


–1


1


3


I got -1 but im not sure

heres my work

4x + 2(x – 3) = 3x + x – 12

4x + 2x - 6 = 3x + x - 12

6x -6 = 3x = 3x + x - 12

6x = 3x = 4x - 18

9x = 4x - 18

13x = -18
18 ÷ 13
make it negative

User Kalila
by
5.1k points

2 Answers

3 votes

The answer is -3, let me know if you want me to give you the steps

User Muhammadalive
by
5.9k points
1 vote

The answer would be -3

User NWaters
by
5.3k points